Student Approaches to Networked Learning and the Role of Evaluation - Diercks-O’Brien, Gabi; Karran, Terence (Proceedings of the International Conference on Networked Learning, 2000)
The objectives of this paper are to discuss the role of evaluation in helping to understand networked learning better and to contribute towards constructing a new paradigm for this new and unexplored mode of learning. Moreover, the preliminary findings of the large-scale evaluation of net worked learning, as part of the Teaching and Learning Technology Programme TLTP3 funded Extended Learning Environment Network (ELEN) Project, will be presented here.